ASSOCIATED FACTORS IN TUBERCULOSIS CONTACT INVESTIGATION: STUDY FROM JANUARY TO SEPTEMBER 2024 IN BOYOLALI DISTRICT, INDONESIA (Proceedings of the Global Public Health Conference, 2025)
Tuberculosis (TB) contact investigation is a crucial part of the TB control strategy. Boyolali District has yet to reach the contact investigation target, with only 21.1% of cases having undergone contact investigation in September 2024, far below the targeted 90%. This study aims to identify factors associated with tuberculosis contact investigation in Boyolali District. Using a cohort retrospective study on bacteriological TB patients registered in the tuberculosis information system from January to September 2024. Individual data (age, gender, residence, history of TB treatment, and HIV status) and health facilities characteristics (ownership and type) were analyzed with chi-square and logistic regression. We found that contact investigation was primarily conducted in aged 31-40 years (24.3%) and 51-60 years (24.3%), male gender (63.5%), living in Boyolali District (94.6%), having no history of TB disease (70.3%), not knowing HIV status (94.6%), seeking treatment at government-owned health facilities (93.2%) at public health centers (75.7%). Chi-square analysis showed that residencies (p-value = 0.02), ownership of health facility (p-value = 0.00), and type of health facility (p-value = 0.01) were associated with case investigation. Logistic regression revealed that patients living in Boyolali District (p- value = 0.03; OR = 3.3; 95%CI = 1.15 – 9.56), those treated at government-owned health facilities (p- value = 0.01; OR = 3.7; 95%CI = 1.42 – 9.52), and those attending public health center (p- value = 0.00; OR = 2.4; 95%CI = 1.34 – 4.40) were more likely to be investigated for tuberculosis contact. Outreach to patients outside the district and those treated at private health facilities, particularly hospitals, is essential for improving TB contact investigation coverage. Furthermore, strengthening health facility coordination, health worker capacity, and regular evaluations are crucial for optimizing investigations and reducing TB transmission.
Keywords: tuberculosis; control program; contact investigation; residences; health facilities; cohort retrospective